Characteristics of behavioral and socioeconomic risk factors for noncommunicable diseases in young people with comorbidities - A. D. Afanaseva; L. V. Shcherbakova; V. V. Gafarov; V. S. Shramko; D. V. Denisova; Yu. I. Ragino (Кардиоваскулярная терапия и профилактика, 2025)
Aim. To analyze behavioral and socioeconomic risk factors for noncommunicable diseases in young people with comorbidities.Material and methods. The population sample included 1415 people. Comorbid pathology was considered a combination of ≥3 diseases. Comorbid pathology was detected in 105 examined people.For comparison with comorbid patients, a group of healthy individuals without any of the studied diseases was formed (n=162).Results. When assessing the main socioeconomic and behavioral characteristics, healthy individuals more often report a good self-perceived health compared to individuals with comorbid pathology, while no differences were found for poor self-perceived health between the groups. Individuals with a combination of ≥3 pathological conditions were more likely to smoke, and also more often had manifestations characteristic of eating disorders, namely abdominal obesity (AO), overweight, class I and II obesity. Morbid obesity was recorded only in individuals with comorbid pathology. According to univariate regression analysis with standardization by sex and age, comorbid pathology was associated with smoking, AO and a good self-perceived health. When including socioeconomic and behavioral characteristics in the regression model, the probability of comorbid pathology increased by >3 times in smokers, slightly <3 times in men, 2,5 times in AO and with a worse self-perceived health, and was also associated with an increase in age by 1 year.Conclusion. Among young people, comorbid pathology is associated with male sex, smoking, AO and a worse health self-perception compared to healthy individuals.